2011
DOI: 10.1111/j.1744-6163.2011.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers with Depression, School-Age Children with Depression? A Systematic Review

Abstract: Identifying mothers with depression may be useful for prevention and early detection of school-age children's depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
0
18
0
8
Order By: Relevance
“…Parental depression is one of the most robustly established risk factors of child and adolescent psychopathology (Brennan et al, 2002;Goodman et al, 2011;Goodman and Gotlib, 1999;Keller and Gottlieb, 2012;Mendes et al, 2012;Weissman et al, 2006;Wickramaratne and Weissman, 1998). A meta-analysis, pooling 121 studies, found a correlation of 0.23 (95% CI, 0.22-0.24) for maternal depression and offspring internalizing problems (Goodman et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Parental depression is one of the most robustly established risk factors of child and adolescent psychopathology (Brennan et al, 2002;Goodman et al, 2011;Goodman and Gotlib, 1999;Keller and Gottlieb, 2012;Mendes et al, 2012;Weissman et al, 2006;Wickramaratne and Weissman, 1998). A meta-analysis, pooling 121 studies, found a correlation of 0.23 (95% CI, 0.22-0.24) for maternal depression and offspring internalizing problems (Goodman et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Childhood depression was the most frequently addressed psychopathology (Goosby, 2007;Lau et al, 2007;Lengua et al, 2008), and this outcome was common among the children of mothers with depression (Mendes, Loureiro, Crippa, et al, 2012). This finding might indicate the transgenerational nature of depression.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, these researchers observed that in the total sample of 1858 participants, morning cortisol was associated with a high risk of depression exclusively in male participants. Given the higher prevalence of depression in adolescent girls (Domench-Llaberia et al, 2009;FonsecaPedrero, Paino, Lemos-Giráldez, & Muñiz, 2011;Mendes et al, 2012;Weissman et al, 2006), these groups of results (Lewis, Jones, & Goodyer, 2016;Nelemans et al, 2014;Owens et al, 2014) should alert us of the need to shift the focus of our attention towards the search for further sensitive biomarkers of early depression risk in girls. In line with this search for new, more precise biological markers of depression, the usefulness of sAA as a low-cost, biological marker of psychopathology has become a relevant new line of research, especially over the two last decades.…”
Section: Introductionmentioning
confidence: 99%